HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN T PADA PESILAT PUTRA PERGURUAN SATRIA MUDA INDONESIA UNIT RUMBAI - Iin Damayanti; .Ramadi '; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observation that has been done against athletes PPLP Pencak Silat Dispora Riau discovered several phenomena such as: is that a T by the athlete is still less than the maximum, this is caused by not the most of the physical elements are like the limb muscles the athlete that was not optimal, so that a T that do not powered. It,s not good balance of the masters, will also affect the speed of a T by masters. Coordination which is owned by athletes are also not optimally, this will affect the T, would be easily anticipated by his opponents with defense, dodgery, and even make it easier for opponents to do behind the attacks quickly and suddenly. The T in the sport of martial arts to do with a limb muscles strong and the ability range on the target to fight hard to do resistence and dodgery. The purpose of this research is to identify how a muscular limbs with a yacht masters, men,s college gentlemanly Indonesia youth unit fringe. This research is done using this type of research correlational. Correlational is a statistical tool, which can be used to compare the results of measurements of two different variables in order to determine the degree of correlation between the variables. The populasi and sample in this study is a member of the masters, men,s college gentlemanly Indonesia youth unit fringe of 15 people. The data collection technique is to use a technique total sampling. Based on the results of research has been done can be concluded that there is to do a limb muscles on the ability of a T on cruise the son of college gentlemanly young Indonesia unit fringe with count r = 0.526 and the significant level = 5% was found r = 0.514 with categories are of a significant connection.Keywords: Leg Muscle Power, The Ability of a T.